Salt-Sensitivity of Blood Pressure and Insulin Resistance - Ertuglu, Lale A.; Elijovich, Fernando; Laffer, Cheryl L.; Kirabo, Annet (Frontiers in Physiology, 2021)
Salt sensitivity of blood pressure (SSBP) is an independent risk factor for cardiovascular morbidity and mortality that is seen in both hypertensive and normotensive populations. Insulin resistance strongly correlates with SSBP and affects nearly 50% of salt sensitive people. While the precise mechanism by which insulin resistance and SSBP relate remains elusive, several common pathways are involved in the genesis of both processes, including vascular dysfunction and immune activation. Vascular dysfunction associated with insulin resistance is characterized by loss of nitric oxide (NO)-mediated vasodilation and heightened endothelin-1 induced vasoconstriction, as well as capillary rarefaction. It manifests with increased blood pressure in salt sensitive murine models. Another common denominator in the pathogenesis of insulin resistance, hypertension and salt sensitivity is immune activation involving pro-inflammatory cytokines like TNF-α, IL-1 and IL-6. In the last decade, a new understanding of interstitial sodium storage in tissues such as skin and muscle has revolutionized traditional concepts of body sodium handling and pathogenesis of salt sensitivity. We have shown that interstitial Na+ can trigger a T cell mediated inflammatory response through formation of isolevuglandin protein adducts in antigen presenting cells, and that this response is implicated in salt sensitive hypertension. The peroxisome proliferator-activated receptor γ (PPARγ) is a transcription factor that modulates both insulin sensitivity and blood pressure. PPARγ agonists increase insulin sensitivity and ameliorate salt sensitivity, whereas deficiency of PPARγ results in severe insulin resistance and hypertension. These findings suggest that PPARγ plays a role in the common pathogenesis of insulin sensitivity and salt sensitivity, perhaps via effects on the immune system and vascular function. The goal of this review is to discuss those mechanisms that may play a role in both salt sensitivity of blood pressure and in insulin resistance.